2009
DOI: 10.1111/j.1399-0004.2008.01131.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of first‐trimester miscarriages with a combination of cytogenetic karyotyping, microsatellite genotyping and arrayCGH

Abstract: Miscarriage is the spontaneous loss of an embryo or fetus before the 20th week of pregnancy. Most miscarriages occur before the end of the first trimester (<13 weeks). Although many risk factors relate to this occurrence, genetic factors play the most important role. Chromosomal abnormalities, including both numerical and structural anomalies, underlie the majority of miscarriages. In this study, we employed a comprehensive approach using cytogenetic karyotyping, polymerase chain reaction (PCR)-based genotypin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
62
1
11

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 41 publications
5
62
1
11
Order By: Relevance
“…The detection of approximately 55% of abnormalities in miscarriage material, without previous selection, is in accordance with data from the literature 4,11 . In a study conducted in China, Zhang et al 4 assessed 115 miscarriage materials and concluded that 61% presented chromosome abnormalities, 90% of which were numerical and 10% of which were structural, underscoring that polymerase chain reaction and comparative genomic hybridization are useful techniques for cases in which there is no cell growth in growth medium or when there is contamination by maternal cells 11 .…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The detection of approximately 55% of abnormalities in miscarriage material, without previous selection, is in accordance with data from the literature 4,11 . In a study conducted in China, Zhang et al 4 assessed 115 miscarriage materials and concluded that 61% presented chromosome abnormalities, 90% of which were numerical and 10% of which were structural, underscoring that polymerase chain reaction and comparative genomic hybridization are useful techniques for cases in which there is no cell growth in growth medium or when there is contamination by maternal cells 11 .…”
Section: Discussionsupporting
confidence: 77%
“…In a study conducted in China, Zhang et al 4 assessed 115 miscarriage materials and concluded that 61% presented chromosome abnormalities, 90% of which were numerical and 10% of which were structural, underscoring that polymerase chain reaction and comparative genomic hybridization are useful techniques for cases in which there is no cell growth in growth medium or when there is contamination by maternal cells 11 . The rate of cell growth failure mentioned in the literature ranges from 10% to 15%, which is in accordance with the rate found in this study (10.7%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,12 The etiologic analysis of pregnancy loss can provide important information for medical management, reproductive counseling, and supportive patient care. 4,13,14 Although fetal karyotyping has been used for many years to evaluate samples of products of conception (POCs), there are two primary limitations to this method. First, cytogenetic analysis requires live cells, which requires culture.…”
Section: Introductionmentioning
confidence: 99%
“…The superior diagnostic power of CMA compared with karyotyping is well established in the pediatric and prenatal literature; however, exploration of the use of this technology for studying POC samples has been somewhat limited to date. 9,10,12,14,15,18,[20][21][22][23][24][25][26][27][28] Specifically, CMA is a particularly attractive technology for use in the study of POC samples because it is performed using extracted cellular DNA, significantly improving the likelihood of obtaining a result. Unlike karyotype analysis, CMA can even be performed on DNA extracted from formalin-fixed and paraffin-embedded tissues (FFPE), a process that is undergone by nearly every POC sample subjected to histopathological evaluation.…”
Section: Introductionmentioning
confidence: 99%